An exploratory study on the word associations of sixth grades to certain science concepts - Garcia, Mirabel S. (1973)
The aim of the study is to determine whether a difference exists between the word association given by sixth graders to certain science word concepts when these are presented in their first language (Ilocano) and in their second language (English). The findings of the study may be used to guide the teachers in selecting and organizing materials for science instruction, in determining methods of teaching, and in learning to adjust these methods and the curriculum to fit the needs, abilities and interests of children.